The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1746-6148-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genomic and proteomic data in recurrent airway obstruction affected horses using ingenuity pathway analysis®

Abstract: BackgroundRecurrent airway obstruction (RAO) is a severe chronic respiratory disease affecting horses worldwide, though mostly in the Northern hemisphere. Environmental as well as genetic factors strongly influence the course and prognosis of the disease. Research has been focused on characterization of immunologic factors contributing to inflammatory responses, on genetic linkage analysis, and, more recently, on proteomic analysis of airway secretions from affected horses. The goal of this study was to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Considering the origin of the Polish Konik horse from a small number of progenitors (21), namely their close relationship, a higher incidence of genetic diseases can be suspected. Several studies have demonstrated a predisposition for RAO in families, and it is now proven that this disease has a genetic background (6,(14)(15)(16)18). In offspring the risk of developing recurrent airway obstruction is three times higher, when one parent is affected with this disease, and increases almost five times, when both parents have RAO.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the origin of the Polish Konik horse from a small number of progenitors (21), namely their close relationship, a higher incidence of genetic diseases can be suspected. Several studies have demonstrated a predisposition for RAO in families, and it is now proven that this disease has a genetic background (6,(14)(15)(16)18). In offspring the risk of developing recurrent airway obstruction is three times higher, when one parent is affected with this disease, and increases almost five times, when both parents have RAO.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of a universally identified pathogenesis likely stems from both the lack of uniformity in the inciting exposures and genetic diversity within and between the relatively small research herds from which the data were derived and the different methodologies used in these studies. Even in RAO, in which the genetic component of disease susceptibility is well established, there is diversity both in the mode of inheritance and the genetically determined immunological pathways recruited in the face of challenge . The negative impact of such diversity on the ability of the clinician to accurately pigeon‐hole specific lower airway diseases in individual animals within a clinical setting is likely to be of even greater significance.…”
Section: Absence Of a Diagnostic ‘Pigeon‐hole’ For Equine Lower Airwamentioning
confidence: 99%
“…Molecular pathway analyses (Ingenuity Pathway Analysis) of genomic and proteomic data showed that interactions between IL4R gene products and another candidate gene ( SOCS5 ) could explain how different genes and genotypes can lead to identical clinical RAO phenotypes: these proteins interact upstream of an important cascade involving nuclear factor kappa B (NFκB) . This combined evidence (Table ) – from genetic association and linkage analyses , gene expression studies and molecular pathway exploration – indicates that IL4R is presently the major candidate gene in a subset of RAO‐affected horses with a specific genetic background. Definitive proof is still lacking, however: it is important to note that so far no causal mutation for RAO has been identified in IL4R .…”
Section: Il4r Is a Major Candidate Genementioning
confidence: 99%